Analisis Hubungan Antara Persepsi Tentang Geoliteracy Terhadap Spatial Ability Peserta Didik (Studi Kasus Peserta Didik Kelas XI IPS MAN 2 Ngawi) - Alfi Roudhotul Husniyah; Ahmad Ahmad; Singgih Prihadi (GEADIDAKTIKA, 2023)
The purpose of this research is to examines (1) the perception of geoliteracy, (2) the level of spatial ability and (3) the relationship between perceptions of geoliteracy and spatial ability in XI IPS class students at MAN 2 Ngawi. This research was developed by using quantitative descriptive study with saturated sampling survey method. The data collection technique used a geoliteracy perception questionnaire and spatial ability test instruments. Based on the research results, it is known that 90% of students have a good perception and 10% of students have a moderate perception. The results of the spatial ability test showed mixed results, namely 35% of students had high spatial abilities, 41% of students had moderate spatial abilities, and 24% of students had low spatial abilities. In the correlation test, it shows that the calculated r value of 0.136799 < r table is 0.220 with a significance value of 0.05. The conclusion of this study is that there is a weak correlation between the perception of geoliteracy on the spatial abilities of students, so it is necessary to improve the quality of learning so that it can build students' spatial abilities.Keywords: perception of geoliteracy, spatial ability, relationship